2018
DOI: 10.1177/0040517518779252
|View full text |Cite
|
Sign up to set email alerts
|

Use of cottonseed protein as a strength additive for nonwoven cotton

Abstract: Nonwoven fabrics have grown in popularity in recent years due to their overwhelming usage in a wide range of consumer products. Cotton-based nonwovens are of particular interest because of their ability to be recycled and reused, resulting in a more environmentally friendly product compared to their petroleum-based counterparts. The current research characterized the use of cottonseed protein as an additive to increase the dry strength of cotton-based nonwovens. The tensile strength of nonwovens was found to i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 22 publications
1
12
0
Order By: Relevance
“…Hydrogenbonding between the amide I carbonyls and cellulose substrates has been previously observed between cellulose and cottonseed protein [30,31] and between nanocellulose and amide carbonyls of polyacrylamide [46]. This hydrogen-bonding could potentially account for some of the increased strength observed in the treated samples (vide infra) [30].…”
Section: Samplementioning
confidence: 77%
See 1 more Smart Citation
“…Hydrogenbonding between the amide I carbonyls and cellulose substrates has been previously observed between cellulose and cottonseed protein [30,31] and between nanocellulose and amide carbonyls of polyacrylamide [46]. This hydrogen-bonding could potentially account for some of the increased strength observed in the treated samples (vide infra) [30].…”
Section: Samplementioning
confidence: 77%
“…Several proteins have been previously reported as binders and strength agents in paper products, such as soy protein [23][24][25][26][27], gelatin, zein, and hydroxyproline-rich glycoprotein [28] and cottonseed protein [29]. Related work has shown that CSP isolate served as an effective strength agent for nonwovens [30]. In an adhesive study, improved performance was observed when CNCs and CNFs were used as strength additives with CSP [31].…”
Section: Introductionmentioning
confidence: 99%
“…In another application, cottonseed protein was used as an additive to increase the dry strength of cotton-based nonwovens [128]. The tensile strength of the nonwovens was found to increase as the concentration of protein applied increased.…”
Section: Other Applicationsmentioning
confidence: 99%
“…4,5 Therefore, developing effective and green textile adhesives to substitute petro-based adhesives attracts more and more interest . 6,7…”
mentioning
confidence: 99%
“…4,5 Therefore, developing effective and green textile adhesives to substitute petro-based adhesives attracts more and more interest . 6,7 With annual production of around 170 million metric tons, soy meal is readily available in large quantities as a co-product from edible oil and biodiesel production, is low cost ($0.18-0.25 per lb), and possesses benign biodegradability. 8 Soy protein isolates (SPI) from soy meal have good biodegradability and filmforming properties, and have been widely used in the field of membranes, textile sizes, adhesives, and biomaterials.…”
mentioning
confidence: 99%